From the sxtA4 Gene to Saxitoxin Production: What Controls the Variability Among Alexandrium minutum and Alexandrium pacificum Strains? - Geffroy, Solène; Lechat, Marc-Marie; Le Gac, Mickael; Rovillon, Georges-Augustin; Marie, Dominique; Bigeard, Estelle; Malo, Florent; Amzil, Zouher; Guillou, Laure; Caruana, Amandine M. N. (Frontiers in Microbiology, 2021)
Paralytic shellfish poisoning (PSP) is a human foodborne syndrome caused by the consumption of shellfish that accumulate paralytic shellfish toxins (PSTs, saxitoxin group). These neurotoxins are produced in marine waters by dinoflagellates of the genera Alexandrium, Gymnodinium and Pyrodinium. In dinoflagellates, PST synthesis is encoded in the nuclear genome via a gene cluster (sxt). In Alexandrium spp., toxin production is associated with the presence of a 4th domain in the sxtA gene (sxtA4), one of the core genes of the PST gene cluster. It is suspected that gene expression in dinoflagellates is partially constitutive, with both transcriptional and post‐transcriptional processes potentially co-occurring. Therefore, gene structure and expression mode are two important features to explore in order to fully understand toxin production in dinoflagellates. During this study, we determined the intracellular toxin contents of twenty European Alexandrium minutum and A. pacificum strains that we compared to their genome size and sxtA4 gene copy numbers. We detected a significant correlation between the sxtA4 gene copy number and toxin content, as well as a moderate positive correlation between the sxtA4 gene copy number and genome size. The 18 toxic strains had more than nine sxtA4 gene copies, whereas only one copy was found in the two non-toxin producing strains. We additionally explored the allelic frequencies and expression of sxtA4 mRNA in 11 A. minutum strains. We observed both a differential expression and specific allelic forms in the non-toxic strains compared to the toxic ones. Also, the toxic strains exhibited a polymorphic sxtA4 mRNA sequence both between strains and between gene copies within strains. Finally, our study was congruent with the hypothesis of a genetic determinism of toxin synthesis (i.e., the existence of several genetic isoforms of the sxtA4 gene and their copy numbers), which is also consistent with the hypothesis that constitutive gene expression and moderation by transcriptional and post-transcriptional regulation mechanisms are the cause of the observed variability in the production of toxins by A. minutum.